(untitled) (Journal of Libya for geographical studies, 2023)
The research aimed to define the marine areas that make up the Libyan marine waters and determine its spatial dimensions, based on the United Nations Convention on the Law of the Sea for the year (1982) and the Libyan legislation for defining the Libyan marine waters and the geographical database of the maritime borders provided by the Flanders Maritime Institute, and to reveal the major topographic features that cover the seabed. The study area, based on the digital elevation model (ETOPO1) provided by the official website of the National Oceanic and Atmospheric Administration of the United States of America. The research concluded that two digital databases were produced for marine areas and major topographic features in the study area, so that the inland waters area constitutes (22%) of the total area of the study area and is an integral part of the territory of the Libyan state over which it exercises full sovereignty. (17%) of the total area of the study area, and both are subject to restricted sovereignty, and the exclusive economic zone constitutes (61%) of the total area of the Libyan marine waters area, and the Libyan state has the right to mandate and supervise many activities in this area, taking into account the interests and rights of other countries in it. The bottom of the study area is characterized by the diversity of its topographical appearance, which could be divided into four major topographical features, varying in terms of depth, erosion, and slope, so that its depths ranged between (0) - (-4057) below sea level, and its slope ranged between (0.3-35) degrees. , so that the depth and slope increase in general towards the north and northeast, from the range of the continental shelf towards the deep plain, and it is covered by thick continental and organic sediments, and its breadth differs from one place to another, and it is directly related to the corresponding topographic features on the continental land, so that its breadth increases and its complexity decreases in The places opposite the plain areas, while its breadth and complexity decreases in the opposite sides of the plateau and mountainous areas.